IMPROVING STUDENTS’ READING COMPREHENSION ABILITY BY USING MAKE A MATCH ASSISTED BY FLASHCARD ON THE VIII CLASS OF SMP IT MADANI IN ACADEMIC YEAR 2021/2022 - FITRIA ISMI ANNUR; MERI VANCITO; SABRUN JAMIL (STKIP USMAN SAFRI KUTACANE, 2023)
This study deals with the students’ ability to improve reading comprehension by using make a match assisted by flashcard on the VIII class of SMP IT Madani Academic Year 2021/2022. Its objective is to find out whether the use make a match assisted by flashcard has a significance improve reading comprehension. Population used in this study of class VIII were 60 and samples used in this study were 30 students. The method used in this study is an experimental method with a one group as pretest and posttest design. This study was carried on using quantitave method. The data was analysed by using t-test. The researcher found the pretest mean = 48,33 , deviation standard = 3,79 and experienced an increase in the posttest mean = 86,67 deviation standart = 4,79. From this analysis, writer found that guided make a match assisted by flashcard has significane in teaching reading comprehension. It can be proved by the result of the analysis showed that “” observed about 34,54 was higher than “ttable” about 2,045 with the level significance is 0,05% it implies that the teacher of English should use make a match assisted by flashcard in teaching reading comprehension so that the teaching and learning process can be successful.